Production of sinthetic varieties and hybrids of corn - Ruschel, Renato (Pesquisa Agropecuaria Brasileira, 2014)
An analysis of yield in commercial plantings of hybrid corn from the corn improvement program of the state of São Paulo, Minas Gerais and Paraná is presented. Sixty eight trials were conducted between 1963/64 and 1967/68. Corn hybrids and synthetic varieties were compared in two distinct climatic regions using average annual production as a basis for the comparison. These regions were (1) south-central region and (2) northeast and eastern coastal regions. The following conclusions were reached: 1. The average yields attained by the varieties in the south-central region were superior to the yields observed in the northeast and eastern coastal region. 2. Reduction of yields in both regions was greater for hybrids than for synthetic varieties. 3. In the northeast and eastern coastal regions the synthetics were superior on the average to the hybrids. 4. Each year better varieties have been tested. 5. Variation in production of the synthetics has been less than for the hybrids. 6. In the south-central region maximum yields were always obtained with the hybrids.